SOA cookbook : design recipes for building better SOA processes : master SOA process architecture, modeling, and simulation in BPEL, TIBCO's BusinessWorks, and BEA's Weblogic Integration /: design recipes for building better SOA processes : master SOA process architecture, modeling, and simulation in BPEL, TIBCO's BusinessWorks, and BEA's Weblogic Integration. (2008) - Unknown
No abstract available